2020
DOI: 10.1038/s41598-020-63491-w
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro analysis of free radical scavenging activities and suppression of LPS-induced ROS production in macrophage cells by Solanum sisymbriifolium extracts

Abstract: The current study aims to evaluate the antioxidant, cytotoxicity activities and suppression of LPSinduced oxidative stress production and characterization of phytochemicals in Solanum sisymbriifolium leaf extracts. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis3-ethylbenzothiazoline-6-sulphonic acid (ABTS) radical scavenging activity of the leaves of S. sisymbriifolium extracted with solvents of various polarities viz. water: ethanol, ratio 50: 50; ethyl acetate and dichloromethane, was assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 26 publications
4
39
0
Order By: Relevance
“…Their results clearly showed that the most active tested extracts and fractions inhibited DPPH • and ROS formations in a dose-dependent manner. A more recent study evaluated the antioxidant activity of several Solanum sisymbriifolium extracts showing that the tested products also demonstrate the ability to scavenge DPPH • and ABTS • and, at the same time, reduce ROS production in a dose-dependent manner [62]. Although these correlations may be difficult to consider due to the complex composition of a plant extract, they are also reported in cases when the antioxidant activity of a single chemical compound is determined.…”
Section: Assessment Of Antioxidant Activitymentioning
confidence: 99%
“…Their results clearly showed that the most active tested extracts and fractions inhibited DPPH • and ROS formations in a dose-dependent manner. A more recent study evaluated the antioxidant activity of several Solanum sisymbriifolium extracts showing that the tested products also demonstrate the ability to scavenge DPPH • and ABTS • and, at the same time, reduce ROS production in a dose-dependent manner [62]. Although these correlations may be difficult to consider due to the complex composition of a plant extract, they are also reported in cases when the antioxidant activity of a single chemical compound is determined.…”
Section: Assessment Of Antioxidant Activitymentioning
confidence: 99%
“…https://doi.org/10.1371/journal.pone.0248491.t004 [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Although the xCELLigence system has been previously used to monitor cell interaction with other bacterial toxins such as Vibrio cholerae toxin [58] and Clostridium difficile toxin [59][60][61][62], to our knowledge, this is the first demonstration of the system suitability to detect PT.…”
Section: Plos Onementioning
confidence: 89%
“…ABTS is a relatively stable free radical and is widely used for measuring antioxidant activity along with DPPH. This method can measure both lipophilic or hypophilic substances ( 30 ). In this study, EAFM improved the ABTS radical scavenging ability.…”
Section: Discussionmentioning
confidence: 99%